Rice Bran Feruloylated Oligosaccharides Activate Dendritic Cells via Toll-Like Receptor 2 and 4 Signaling - Lin, Chi; Chen, Hua; Chen, Yu; Chang, Hung; Lin, Ping; Pan, I-Hong; Chen, Der-Yuan; Chen, Chuan; Lin, Su (Molecules (Basel, Switzerland), 2014)
This work presents the effects of feruloylated oligosaccharides (FOs) of rice bran on murine bone marrow-derived dendritic cells (BMDCs) and the potential pathway through which the effects are mediated. We found that FOs induced phenotypic maturation of DCs, as shown by the increased expression of CD40, CD80/CD86 and MHC-I/II molecules. FOs efficiently induced maturation of DCs generated from C3H/HeN or C57BL/6 mice with normal toll-like receptor 4 (TLR-4) or TLR-2 but not DCs from mice with mutated TLR4 or TLR2. The mechanism of action of FOs may be mediated by increased phosphorylation of ERK, p38 and JNK mitogen-activated protein kinase (MAPKs) and increased NF-kB activity, which are important signaling molecules downstream of TLR-4 and TLR-2. These data suggest that FOs induce DCs maturation through TLR-4 and/or TLR-2 and that FOs might have potential efficacy against tumor or virus infection or represent a candidate-adjuvant approach for application in immunotherapy and vaccination.